Resolver a expressão numérica: -3 – [8 . 9 + ( - 16 : ( - 16) . 8 – 3) + 1 ] = (deverá aparecer todo o desenvolvimento *
Soluções para a tarefa
Respondido por
2
Resposta:
- 81
Explicação passo-a-passo:
- 3 – [8 . 9 + ( - 16 : ( - 16) . 8 – 3) + 1 ] =
- 3 - [72 + (1 . 8 - 3) + 1] =
- 3 - [72 + (8 - 3) + 1] =
- 3 - [72 + 5 + 1] =
- 3 - 78 =
- 81
Perguntas interessantes
Matemática,
9 meses atrás
Contabilidade,
9 meses atrás
História,
11 meses atrás
Pedagogia,
11 meses atrás
Química,
1 ano atrás
Física,
1 ano atrás